Research of microprofile impact on variable transmission’s friction elements on the coefficient of friction in the contact zone and transmission efficiency - Generalova, A.A.; Zverovshchikov, A.E.; Nikulin, A.A. (Известия высших учебных заведений. Поволжский регион:Технические науки, 2023)
Background. Modern requirements for passenger cars include a number of main directions: efficient use of energy, improvement of environmental indicators, improvement of operational characteristics. The use of variator gearboxes has significantly improved the energy efficiency and environmental performance of the car due to optimal engine performance. However, the disadvantage of variators in comparison with manual transmissions is still insufficient efficiency, which does not allow competing with “mechanics” due to low performance characteristics. Since the variator is a friction mechanism, a way to increase the efficiency of its operation is to change the coefficient of friction in friction pairs. One of the options for such modernization is the creation of a regular microprofile on the surface of friction pulleys, namely– undulations. The actual contact spots formed by the undulation provide sufficient traction of the variator transmission and minimize power loss. The object of the study is the relationship between power indicators and the quality of the surface layer of friction elements of a continuously variable transmission. The subject of the study is an adequate assessment and provision of the power parameters of a continuously variable transmission, by ensuring the surface quality parameters of the drive pulley of the variator. The purpose of the study is to develop a technique for providing power indicators of a variator transmission by creating a wavy microprofile based on the mechanics of contact interaction. Materials and methods. The theoretical and experimental research carried out in the work is based on the study of literature, conducted research and the experience of practicing technologists. Results. The empirical dependence of the prediction of the coefficient of friction at normal wear depending on the parameters of surface quality is analyzed. It is shown that the parameters of the undulation of the surface have a greater influence on the coefficient of friction, and as a consequence, the traction ability of the transmission in the frictional interaction of parts, than the roughness parameters. Analytical dependences of determining the power on the output shaft of the variator and the efficiency of the variator depending on the height parameter of the waviness are proposed. Conclusions. Based on the conducted research and experiments, a mathematical model is proposed to ensure the power parameters of variators by forming a high-altitude waviness index. This will make it possible to predict and ensure the coefficient of friction of the friction pair at the stage of development work and drawing up the technological process of processing parts.